2019
DOI: 10.1002/pi.5755
|View full text |Cite
|
Sign up to set email alerts
|

Barium titanate‐based nanodielectrics of two chemically recyclable thermosets

Abstract: In this work was investigated the effect of the addition of barium titanate (BaTiO3) on electrical properties of two chemically recyclable thermosets, polyhemiaminal (PHA) and polyhexahydro‐s‐triazine (PHT), both fabricated from 4,4′‐oxydianiline (ODA), an ether derivative of aniline and paraformaldehyde. Thermal and mechanical properties as well as chemical recyclability of the two polymers and their nanocomposites/nanodielectrics were also investigated. In addition, a quantitative analysis was conducted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…While García et al 3 . and Bello et al 10 . performed PHT synthesis using the ODA monomer and verified T g values of 222 and 180 °C, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…While García et al 3 . and Bello et al 10 . performed PHT synthesis using the ODA monomer and verified T g values of 222 and 180 °C, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The two techniques are different; however, the values obtained for the elasticity modulus are similar to those reported in this work. Bello et al 10 . carried out the synthesis of PHT using the monomer ODA and obtained a reduced modulus of 4.5 GPa by nanoindentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research programmes have been reported in connection with the fabrication of flexible polymeric materials with enhanced dielectric and piezoelectric features. [5][6][7][8] Flexible piezoelectric materials are exploited as pressure sensing devices in biomedical applications. 9 Developing piezoelectric materials compatible with biological systems is an interesting area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a smart material with good flexibility and electronic properties is a challenge for material scientists. Different research programmes have been reported in connection with the fabrication of flexible polymeric materials with enhanced dielectric and piezoelectric features 5–8 . Flexible piezoelectric materials are exploited as pressure sensing devices in biomedical applications 9 .…”
Section: Introductionmentioning
confidence: 99%